Delay As (Non)Foundation of Bureaucracy - Habdankaitė, Daina (Filosofia, 2017)
This paper addresses the problematic nature of bureaucratic power structures and their effectiveness. The paper argues that delay constitutes the essence of bureaucratic power and has controlling effects on all of the three temporal modes – past, present, and future – that individuals are subjected to. The exteriorized and exteriorizing nature of temporal consciousness in particular is showcased thanks to Bernard Stiegler’s conception of the relation between technics and time. By discussing Franz Kafka’s fiction as well as the most common bureaucratic encounters, the paper argues that both the formal and the repetitive character of bureaucratic procedures are not only facilitated but even presupposed by the constitution of temporal consciousness, which is prone to temporal delay and to the controlling mechanisms that come along with it.